PENERAPAN METODE INQUIRY DIPADU TRIK TAKTIK WAKTU BERTANYA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR KONSEP SEL PADA SISWA KELAS VII SMP KARTIKA AMBON - Jeli Samadara; S I. A. Salmanu (BIOPENDIX, 2018)
Background: Inquiry method is a method that can stimulate students to find their own answers to problems that students face in class. Through this learning method students can mobilize all abilities and knowledge they have, in finding answers to existing problems, so students can think critically in the learning process. Method: This study was conducted in class VII1 in the Kartika Middle School in Ambon. This study uses descriptive analysis that is used to determine critical thinking skills and cognitive, affective, and psychomotor learning outcomes of students. Results: The study showed that mastery of cell concepts in students before the application of the Inquiry method combined with tactics tricks when asking was very low. This can be seen from the percentage of the average score obtained by students in the initial test which is 31% which includes failed qualifications because it does not reach the KKM which is set at 75. After the application of the Inquiry method combined with tactics when asking questions, the results of the formative tests obtained by students increase with the average percentage of achievement is 71.51%. To assess students 'critical thinking skills through worksheets and observation sheets, the results show that there is an increase in students' critical thinking skills. Conclusion: The application of the Inquiry method combined with tactics when asking questions can improve students' critical thinking skills and achievement of learning outcomes in cell concept biology.